WEBINAR EDUKASI PENINGKATAN PENGETAHUAN DISKURSUS PENTAKOSTA BAGI KOMUNITAS ASPENKRIS - Junifrius Gultom; Gernaida Krisna R. Pakpahan; Frans Pantan; Valentino Wariki (Jurnal PKM Setiadharma, 2022)
The Pentecostal academic community is responsible for echoing Pentecostal theology and spirituality for the local congregation. However, the courage and ability to carry out this responsibility must continue to be improved through training and mentoring. This activity aims to increase the inventory of Pentecostalism discourse for Pentecostal and Ecumenical scholars through the implementation of a dissertation seminar in the Pentatalk program by the Association of Indonesian Pentecostal/Charismatic Scholars (Aspenkris). Dissertation studies from Pentecostal academics will strengthen their identity as Pentecostalists for teachers. The implementation method is an educational webinar through the Zoom meeting platform. The activity results show that, firstly, providing a broad discourse and discourse on pentecostalism both in Indonesia and abroad must be carried out immediately. Second, this activity can reduce the stigma and understanding of Pentecostalism, which is dwells on the Holy Spirit alone. Third, this activity establishes and increases the dialogue between Pentecostalism and ecumenicalism, which is still minimal among theologians and ecclesiastical practitioners.